Islamic work ethic and public sector innovation: entrepreneurial orientation as a moderator - Muliati, Usman (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2017)
Link to publisher's homepage at http://ijbt.unimap.edu.my